Educational communication as a factor for (re)valorization of the archaeological Heritage - good practices in Portuguese archeology museums (2014) (Cadernos de Sociomuseologia, 2014)
In this research work we analyzed the educational communication as a means of (re) valorization of the archaeological heritage through examples of good practice in Portuguese museums of archaeology. In the theoretical and methodological framework applied to the thesis, we describe the conceptual architecture and key concepts (communication, education, educational communication and good educational practices in museums, (re) valorization of the archaeological heritage and museums of archaeology). We created a new study model, which we called participatory archaeological museology, based on the principles of Sociomuseology and musealization of archaeology and on the transversality of the archaeological heritage. The participatory archaeological museology aims to build communication strategies and learning environments expressed in communicative and educational activities, in the sense of making visitors more active and participative, through mediation, museography and museographic resources. Thus, the final objective is to make the museum a learning and participatory centre, where visitors can make their own learning paths and knowledge production. We developed a reflective analysis on the history of Museums of Archaeology. We analyzed the evolution of concepts and typologies of museums of archaeology. We have identified several types of archaeological museum spaces and proceeded to its census until 2013. Concerning the strategies of educational communication, we have conducted a comparative research between in-person and distance strategies of educational communication used in archaeological museums. Finally, we have identified and made a comparative analysis of good practices in educational communication in Portuguese Archaeological Museums. Thus, in addition to the added value of these good practices, we have pointed the way to how they can articulate in a network. Only in this way can good practice go from the exception to become the reality and contribute, in an assertive way, to the (re) valorization of the archaeological heritage, involving visitors and their communities, i.e. by returning the participatory heritage as collective memory to the society itself. Keywords: educational communication, archaeological heritage, museums of archaeology, learning, participatory museum